Investigation of anisotropic reflectance from densified arrays of vertically aligned carbon nanotube forests (VACNTs) - Rana, Masud; Mohd Asyraf, M. R.; Saleh, Tanveer; Asan Gani, Abdul Muthalif (Elsevier Ltd., 2016)
VACNTs is commonly known as darkest absorber on earth owing to their highly inherent porosity. To reduce this porosity, in this letter, we introduce a simple process to densify VACNTs by soaking into water. Later on, the VACNTs was dried at ambient temperature, which made VACNTs more compacted due to their capillary action. Optical characterization of the densified CNT forest was carried out. It was observed that at a fixed incident angle 70 with P-polarized incident light, densified CNT forest shows enhanced reflectance with anisotropic behavior as compared to bare CNT forest.